PENGARUH KONTEN TIKTOK EDUKASI TERHADAP LITERASI DIGITAL DAN MINAT BELAJAR SISWA SEKOLAH DASAR (SD) - Arini, Siti; Asep Sahrul Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology, particularly the social media platform TikTok, has significantly impacted the learning process of elementary school students. This study aims to analyze the influence of educational TikTok content on digital literacy and learning interest in elementary school students. The research method used a qualitative approach with a Systematic Literature Review (SLR). Data were obtained from SINTA-indexed scientific articles through the Google Scholar database, published between 2020 and 2025. The article selection process was carried out systematically using inclusion and exclusion criteria, resulting in 12 relevant articles. Data analysis used content analysis through the stages of data reduction, data presentation, and conclusion drawing. The study results indicate that educational TikTok content contributes positively to improving students’ digital literacy, particularly in their ability to access, understand, and evaluate information. Furthermore, educational content can also increase learning interest through visual, interactive, and contextual presentation. However, uncontrolled use has the potential to negatively impact learning focus and interest. Therefore, educational TikTok has the potential to be an innovative learning medium if used wisely and with direction.